The Effectiveness of the Role of the Regional Disaster Management Agency (BPBD) in Handling COVID-19 in Gorontalo Provinc - Fachry Hidayat Katili; Moh.Subhan Lapasau; Dhiva Nandhita Mohune; Syaefullah (IHSA Institute, 2022)
Disaster is an event that can threaten and disrupt people's lives and livelihoods. As is happening now, namely the Corona Virus (COVID-19) disaster which has spread throughout the world. 1. The research objective is the role of BPBD in dealing with covid-19 in Gorontalo Province 2. To analyze the obstacles and obstacles faced by BPBD in handling covid-19. By using a qualitative research approach that is useful for describing how effective the Regional disaster management agency is in dealing with the Covid-19 outbreak in Gorontalo Province. This analysis technique basically consists of 3 components, namely data reduction, data presentation and withdrawal and testing of conclusions using two data sources, namely primary and secondary data. The conclusion is that the achievement of vaccination results in Gorontalo province has been growing with assistance from related parties, especially assistance from the Regional Disaster Management Agency which has made BPBD more effective in carrying out its role as secretariat of the Task Force for the Acceleration of Handling Covid-19.